STORY TRHOUGH APPLYING OF THINK PAIR SHARE LEARNING MODEL - Reza Fachrudin Zuhdi; Rukayah Rukayah; Kuswadi Kuswadi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The purpose of this study’s to improve children's story reading comprehension skills by applying the think pair share learning model. CAR takes place in two cycles, each cycle consists of 2 meetings and 4 stages. The subjects of this study are classroom teachers and students of grade V SD Negeri Karangasem 4 No.204 Surakarta 2017/2018 academic year. Data analysis technique used is interactive analysis model from Miles&Hubberman. Technique of validity test in this research use triangulation technique and triangulation of source. The conclusion of this research that is model of think pair share can impove reading comprehension skill of child story.